Perancangan Sistem Informasi Stok Barang dan Laporan Penjualan pada Online Shop Meeclo Berbasis Mobile Android - Sandi Ferdiansyah; Heri Haerudin (Jurnal Informatika Universitas Pamulang, 2022)
Meeclo Store is an UMKM business engaged in the sale of women's clothing, located in Depok, West Java. The problem faced in the current system is that the processing of goods data, administration and printing of reports using the xls format in Microsoft Office Excel is still an obstacle for employees and shop owners, because the current format is still limited, including in processing data. Both employees and owners can manage all existing data without any restrictions to employees, so that privacy matters are known by employees. The second thing is there are still human errors experienced during the operation. The third thing is that the printing of the report must first filter the required data,so that it takes a long time. In addition of these three things, the current owner also needs an operating system that can be used flexibly and efficiently in data processing. Therefore, the author makes an information system that is appropriate and needed by the problems faced by the Meeclo store owner. In this study the author used the Waterfall method as a reference in the process. The information system produced in this study can process incoming and outgoing transaction data to make various types of reports that are easy and fast.